The effect of winter swimming on body's external temperature - Anna M. Bach; Dariusz Dziarkowski; Szymon Gawrych; Tetiana Yermakova (Physical Education of Students, 2021)
Background and Study Aim. The main aim was to compare the changes in external body temperature of students who gave in an immersion of winter swimming.